La gestión de cobranzas y su impacto en la rentabilidad financiera de la Cooperativa de Ahorro y Crédito PAIS Ltda., agencia matriz Riobamba, 2022 - Saldaña Muñoz, Dilan Jaqueline (2024)
ABSTRACT: Collection management is essential in organizations to take care of their liquidity and continuity. For this reason, it allows to maintain financial health efficiently, a competent management helps to reduce delinquencies by having adequate cash flow. However, many financial entities carry out inadequate collection management, leading to debt recovery and non-payment problems. In this context, this study aims to evaluate the collection management of the Cooperativa de Ahorro y Crédito PAIS Ltda. and its impact on financial profitability by 2022; due to a low proportion in collection management, analyzing the year 2021 in relation to the year 2022. This study is a comprehensive field and documentary investigation, conducted at a descriptive level. It follows an inductive-deductive methodology and a mixed approach, combining the application of interviews as a data collection instrument with the analysis of primary sources. The study population and sample consist of 7 individuals working in the entity. The aim is to identify similarities, differences, causes, effects, and possible solutions to the research problem. The results obtained through the application of indicators such as: Compliance, Effectiveness and collection actions, demonstrate progress for the year under study 2022, in relation to the year 2021, being its application essential for collection management, which directly impacts the financial profitability of financial entities. Keywords: Indicators, Collection Management, Credits, Financial Statements, Profitability